Efficacy of an Assistive Device for Museum Access to Persons with Hearing Impairment - Ajish K. Abraham (Journal of All India Institute of Speech and Hearing)
Museum is a place of learning. Visit to the museum will be fruitful through e ective interaction with the curator. Acoustic barriers in the museum prevent the curator’s speech being intelligible to persons with hearing impairment. An assistive device was developed at AIISH to overcome the acoustic barriers for museum visitors with hearing impairment. The eld trials of the device were conducted at the Regional Museum of Natural History, Mysuru. The study reported in this paper quanti es and critically evaluates the ecacy of the device in overcoming the acoustic barriers and making curator’s speech audible and intelligible to the visitor. The ecacy measures employed were measurement of acoustic variables and feedback of the user through questionnaire. The results showed that, the device has been e ective in overcoming the acoustic barriers for all visitors with hearing impairment, irrespective of their degree of hearing loss and the type of the hearing aid. The device has followed a universal design and hence is useful to all visitors to the museum.